Accumulation of water rights in Peru - Hendriks, Jan (2016)
In Latin America, water governance is facing the problem of rising demand for water resources, increased hydrological variability in a context of climate change, proliferating contamination and thus —in general— increasing scarcity of water in terms of quantity, quality, and opportunity. This creates competition and conflicts among stakeholders. The issue coincides with the urgent international problem of concentration of land, which is heavily intertwined with the concentration of water in the hands of the few. Globalization and a neoliberal political climate facilitate that powerful actors accumulate water rights and volumes at the expense of less powerful water users. This paper examines some exemplary situations in Peru. It is based on literature review, reports and archival research. The paper concludes that the unfair distribution of land and water, at the expense of rural families, communities and indigenous territories, constitutes a serious threat to environmental sustainability, water security and food security.